Galectin‐3 exacerbates ox‐LDL‐mediated endothelial injury by inducing inflammation via integrin β1‐RhoA‐JNK signaling activation. Issue 7 (10th December 2018) - Chen, Xiumei; Lin, Jianzhong; Hu, Tingting; Ren, Zhiyun; Li, Linnan; Hameed, Irbaz; Zhang, Xiaoyu; Men, Chen; Guo, Yan; Xu, Di; Zhan, Yiyang
Abstract: Oxidized low‐density lipoprotein (Ox‐LDL)‐induced endothelial cell injury plays a crucial role in the pathogenesis of atherosclerosis (AS). Plasma galectin‐3 (Gal‐3) is elevated inside and drives diverse systemic inflammatory disorders, including cardiovascular diseases. However, the exact role of Gal‐3 in ox‐LDL‐mediated endothelial injury remains unclear. This study explores the effects of Gal‐3 on ox‐LDL‐induced endothelial dysfunction and the underlying molecular mechanisms. In this study, Gal‐3, integrin β1, and GTP‐RhoA in the blood and plaques of AS patients were examined by ELISA and western blot respectively. Their levels were found to be obviously upregulated compared with non‐AS control group. CCK8 assay and flow cytometry analysis showed that Gal‐3 significantly decreased cell viability and promoted apoptosis in ox‐LDL‐treated human umbilical vascular endothelial cells (HUVECs). The upregulation of integrinβ1, GTP‐RhoA, p‐JNK, p‐p65, p‐IKKα, and p‐IKKβ induced by ox‐LDL was further enhanced by treatment with Gal‐3. Pretreatment with Gal‐3 increased expression of inﬂammatory factors (interleukin [IL]‐6, IL‐8, and IL‐1β), chemokines(CXCL‐1 and CCL‐2) and adhesion molecules (VCAM‐1 and ICAM‐1). Furthermore, the promotional effects of Gal‐3 on NF‐κB activation and inflammatory factors in ox‐LDL‐treated HUVECs were reversed by the treatments with integrinβ1‐siRNA or the JNK inhibitor. We also found that integrinβ1‐siRNA decreased the protein expression of GTP‐RhoA and p‐JNK, while RhoA inhibitor partially reduced the upregulated expression of p‐JNK induced by Gal‐3. In conclusion, our finding suggests that Gal‐3 exacerbates ox‐LDL‐mediated endothelial injury by inducing inflammation via integrin β1‐RhoA‐JNK signaling activation. Abstract : Our findings identified galectin‐3 deceases cell viability, promotes apoptosis and enhances the expression of oxidized low‐density lipoprotein (ox‐LDL)‐induced inﬂammatory factors, chemokine and adhesion molecules in ox‐LDL‐treated human umbilical vascular endothelial cells (HUVECs). Galectin‐3 induced expression of inflammatory cytokines, chemokines and adhesion molecules plays a promotional role in ox‐LDL induced HUVECs injury by activating integrinβ1‐RhoA‐JNK pathway.